Species Composition of Mosquitoes of Attapeu Province, Lao People's Democratic Republic - Vythilingam, I.; Sidavong, B.; Thim, C.S.; Phonemixay, T.; Phompida, S.; Jeffery, J. (2006)
A list of mosquitoes collected from Lao People's Democratic Republic (Lao PDR) from May 2002 to August 2004 is presented. A total of 8,945 mosquitoes belonging to 14 genera and 57 species was collected. The genera recorded were Aedes, Anopheles, Armigeres, Coquillettidia, Culex, Diceromyia, Downsiomyia, Fredwardsius, Mansonia, Neomelaniconion, Ochlerotatus, Paraedes, Stegomyia, and Verrallina. Seventeen species are first reports for LAO PDR.